Efficacy of purified pectinase obtained from paecilomycesvariotii in extraction and clarification of juice From grapes and pomegranate fruits - NISHA M. K. (International Journal of Pharma and Bio Sciences, 2016)
The present investigation was carried out to study the application and the competitiveness of commercial and purified pectinase obtained from Paecilomyces variotii. The fruit juices (grapes and pomegranate) were carried out at different enzyme concentrations (0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5) and incubation time (30, 60, 90, 120 and 160 minutes) at constant temperature (50ºC) to optimize the enzymatic treatment for the yield and clarity of the juices. The optimum conditions recommended for enzymatic (crude, purified and commercial pectinase) treatment for clarification and yield of fruit juices were 3.5 mg/20g pulp of enzyme concentration and 180 min incubation time at a constant temperature of 50ºC. It was observed that purified pectinase obtained from pectinolytic fungus, P. variotii enhanced juice yield and clarity of grape and pomegranate juices and is on par with the commercial pectinase when compared to untreated juices. A maximum yield of 79% and clarity of 19.4 and 19.5% were obtained from grape juice and a significantly high yield of 74% and clarity of 4.9 and 4.8 were acheived from pomegranate juice when compared to the unclarified grape and pomegranate juices (60 and 52% respectively). There was an increase in the yield of 31.6% and 42.3% of the grape and pomegranate juices respectively when treated with purified enzyme than the untreated juices.